Between Roman culture and local tradition : Roman provincial coinage of Bithynia and Pontus during the reign of Trajan (98-117 AD) - Zajac, Barbara (2023)
Offering a detailed analysis of the Roman provincial coinage of Bithynia and Pontus during the reign of Trajan (98-117), this book characterises individual mints, the rhythm of monetary production, iconography and legends, and considers the attribution and dating of individual issues.